THE STUDENT-TEACHERS’ ATTITUDES TOWARD EFL LEARNING - Daniar Sofeny (Edulitics (Education, Literature, and Linguistics) Journal, 2018)
This paper outlines the results of a survey which was carried out, to identify English Study Program UNIROW Tuban students’ attitudes towards learning the English language as a foreign language. The study investigated students’ motivation in terms of three motivational constructs: instrumental motivation, integrative motivation and personal motivation. In determining what attitudes college students at UNIROW have towards learning English as a foreign language. The 30 students involved in this project were from 2017A class. The students were asked to explain why they wished to become English teachers. A questionnaire and interviews were used for data collection. The students’ reasons for studying English revealed a wide array of attitudes and motivations. Surprisingly, almost half of the students exhibited negative attitudes towards learning English and entering the teaching profession. Other students demonstrated more positive attitudes. Personal reasons were also regarded as important motives by the students. However, regarding the integrative reasons, the results provided evidence that learning English as a part of the culture of its people had the least impact in students’ English language motivation. On the other hand, the data for the students’ attitudes revealed that most of students had positive attitudes towards the social value and educational status of English. Finally, some pedagogical implications that would help tap the students’ motivation and attitudes were presented. Key Words: Attitudes, Foreign Language, Learning English.